RETHINKING RUSSIAN MISSION IN SYRIA - Sevim, Tugce Varol; Ozel, Merve Sune (European Scientific Journal, ESJ, 2013)
Since the collapse of the USSR, Syria has remained to be center of Russian Middle East foreign policy regarding its economic and political ties. As a result of the Arab Spring, the Syrian regime and President Assad has shaken with the unrestrained uprisings and western sanctions and eventually crisis turned into a fierce civil war. From the inauguration of the crisis Russia has never altered its political view on Syria even though there were expectations to the contrary. Moscow officially remained calling for “No military intervention against Syria” and that’s why three times vetoed US resolutions concerning widening sanctions or allowing multilateral military operations. However, Russia claims that Moscow is not protective of Syrian regime or Assad instead prevents Syria to fall into a long-term civil war. On the other hand, Syria is one of the most crucial arms importer of Russia and hosting Russian naval base on its Mediterranean coast. In this paper it is aimed to analyze the Russian stable and consistent foreign policy on Syria and its reasons as well as latest Russian and US rising tensions.